ANALISIS PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM PENGRAJIN KAYU BATIK DESA WISATA BOBUNG KABUPATEN GUNUNGKIDUL - Bayu Wilopo, Kartika Hendra TS & Yuli Chomsatu Samrotun (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
Accounting information can help MSMEs in making economic decisions in order to achieve business success. This study aims to find out the level of use of operating information, management accounting information, and financial accounting information on MSME batik wood craftsmen in the bobung tourism village, patuk sub-district, gunungkidul district. This type of research is a case study. Data obtained by questionnaire and interview techniques. The data analysis technique used by the author is a descriptive analysis method with a quantitative approach. The results of data analysis and discussion show that MSMEs of woodworking craftsmen in bobung tourism villages know about accounting information in general, but do not use it maximally. Keywords: Accounting Information, SMEs, Wood Batik Industry